2017
DOI: 10.1161/circulationaha.116.023527
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Dysfunction Switches Mesenchymal Stromal Cells Toward an Inflammatory Phenotype and Impairs Their Reparative Properties Via Toll-Like Receptor-4

Abstract: The environment of the failing and infarcted myocardium drives resident and transplanted MSCs toward a proinflammatory phenotype and restricts their survival and reparative effects in a mechanism mediated by .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 45 publications
4
41
0
Order By: Relevance
“…Accumulating experimental and clinical data has shown that CSC transplantation can effectively treat MI [ 8 , 42 ]. However, after adoptive transfer, CSCs encounter various undesirable conditions including oxidative stress and inflammatory reactions [ 17 , 43 ]. Pathological stimulation causes functional mitochondrial disruption and consequently results in excessive ROS generation; ROS, in turn, deteriorate mitochondrial dysfunction and amplify mitochondrial apoptosis activation in a positive feedback loop [ 44 ], decreasing cell viability and thereby compromising therapeutic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating experimental and clinical data has shown that CSC transplantation can effectively treat MI [ 8 , 42 ]. However, after adoptive transfer, CSCs encounter various undesirable conditions including oxidative stress and inflammatory reactions [ 17 , 43 ]. Pathological stimulation causes functional mitochondrial disruption and consequently results in excessive ROS generation; ROS, in turn, deteriorate mitochondrial dysfunction and amplify mitochondrial apoptosis activation in a positive feedback loop [ 44 ], decreasing cell viability and thereby compromising therapeutic activities.…”
Section: Discussionmentioning
confidence: 99%
“…These differences could be explained by the fact that the MSC lifetime is dependent on the context they are put into because the environment where MSCs are implanted is decisive for their survival. 48,49 Likewise, different mouse models also present diverse grades of severity and disease progression. The Tg-ATXN3-69Q MJD model is extremely severe because it bears the truncated form of the human ataxin-3 protein, meaning that the achievements obtained in this model would probably represent the worst-case scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stromal cells have been proven to possess immunomodulatory and antiinflammatory properties. 20 Currently, human MSCs hold great promise in regenerative medicine for the therapy of human diseases. [14][15][16] Human MCSs can be acquired from many tissues, such as umbilical cord, bone marrow, and chorionic membrane.…”
Section: Discussionmentioning
confidence: 99%